Un caso de actinomicosis cervicofacial por Actinomyces bovis - Hidalgo R., Walter; Xirinachs de Hidalgo, Hilda; Cappella R., Enrique; Solano, Elfrén (Revista de Biología Tropical, 1960)
The first Costa Rican case of cervicofacial actinomycosis caused by A. bovis is presented from the clinical, bacteriological and mycological standpoints. The case was treated successfully with Griseofulvin (Schering).